Evaluation of the Correlation between Serum Concentrations of Asymmetric Dimethylarginine and Corrected TIMI Frame Count in Patients with Slow Coronary Flow. (19th September 2020) - Naserifar, Mahshid; Ataei, Mahshid; Behzadian, Nadia; Mohammadpour, Amir Hooshang; Dastani, Mostafa; Sahebkar, Amirhossein; Hosseinjani, Hesamoddin
Abstract : Coronary slow flow (CSF) is an important angiographic entity that is characterized by delayed opacification of coronary arteries in the absence of epicardial occlusive disease. Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthase. Elevated levels of ADMA cause the induction of endothelial dysfunction and thus promote atherosclerosis. This study was aimed at determining the role of ADMA in the development of CSF. One hundred twenty-nine subjects who fulfilled the inclusion criteria were enrolled in this study. According to coronary angiography results, these subjects were divided into five groups. The serum concentration of ADMA was measured in these subjects. In this study, there was no significant correlation between serum concentrations of ADMA and mean corrected TIMI frame count (CTFC) (P > 0.05 ). However, the ADMA level was significantly correlated with CTFC in the left anterior descending (LAD) coronary artery in patients with CSF (r = − 0.381, P = 0.045 ). Also, plasma ADMA levels were significantly higher in patients with CSF and without CAD compared to patients without CSF and with CAD (50-90%) (P = 0.034 ). Besides, serum concentrations of ADMA were significantly higher in subjects with BMI < 25 kg/m 2 compared with those having BMI > 30 kg/m 2 (P = 0.003 ). It was also shown that the levels of ADMA were significantly higher in subjects with age as a cardiovascular risk factor compared with those without this risk factor (P = 0.024 ). Further studies with larger population sizes are needed to confirm the present findings on the association between the serum concentrations of ADMA and CSF.